SOCIAL ACTIVITY OF RURAL WOMEN IN UZBEKISTAN: REFORMS, EXPERIENCES AND PROSPECTS IN THE FIELD OF ENTREPRENEURSHIP (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the issues of social and economic support for women in Uzbekistan during the years of independence, with particular attention to women living in rural areas, increasing their social participation, and developing women’s entrepreneurship. The study highlights state policy, the legal and regulatory framework, and practical mechanisms aimed at promoting women’s entrepreneurship. It also presents examples of measures implemented to ensure employment in remote regions, provide vocational training, and develop handicrafts and home-based work. In addition, the article scientifically summarizes certain challenges related to women’s employment, education, health, and legal protection, as well as possible ways to address them. The role of women’s entrepreneurship in societal development is emphasized, and systematic approaches and practical recommendations for further improvement in this field are proposed.
Keywords: Women, rural women, women’s entrepreneurship, employment, vocational training, handicrafts, home-based work, social participation, state policy, socio-economic development, legal protection.